Temporal and spatial variation of fish community and their nursery in a tropical seagrass meadow - Du, Jianguo; Wang, Yanguo; Peristiwady, Teguh; Liao, Jianji; Makatipu, Petrus Christianus; Huwae, Ricardo; Ju, Peilong; Loh, Kar Hoe; Chen, Bin (Springer Verlag, 2018)
Fish species composition and spatio-temporal variability of the community were studied in a tropical seagrass meadow located in a lagoon in the eastern part of North Sulawesi. The diversity of fish community in the seagrass meadows was relatively high, with the Shannon-Wiener index ranging from 1.57 to 3.69. The family Apogonidae was the most dominant in abundance (8.27 ind./(100 m2)) and biomass (28.49 g/(100 m2)). At the species level, Apogon lateralis and Sphaeramia orbicularis were the most dominant species in abundance and biomass, respectively. For spatial distribution on species, the end, middle and mouth of the lagoon clustered together as a whole, which may be due to the substrate types found in those zones. The fish species, fish abundance and fish biomass were greater in the dry and wet seasons than in the transition season, which is explained by the strong monsoon, which provides a more suitable environment and food for the fish. The maximum length of 93.10% of the captured species was less than their length at maturity, indicating that seagrass meadows are nursery habitats for many fishes. Therefore, protection of the seagrass meadows is essential for fisheries and sustainable resource utilization.